Phosphorus limitation, soil‐borne pathogens and the coexistence of plant species in hyperdiverse forests and shrublands - Laliberté, Etienne; Lambers, Hans; Burgess, Treena I; Wright, S. Joseph (The New phytologist, 2015)
507 I. 507 II. 509 III. 510 IV. 510 V. 512 VI. 516 VII. 518 518 References 518 SUMMARY: Hyperdiverse forests occur in the lowland tropics, whereas the most species‐rich shrublands are found in regions such as south‐western Australia (kwongan) and South Africa (fynbos). Despite large differences, these ecosystems share an important characteristic: their soils are strongly weathered and phosphorus (P) is a key growth‐limiting nutrient. Soil‐borne pathogens are increasingly being recognized as drivers of plant diversity in lowland tropical rainforests, but have received little attention in species‐rich shrublands. We suggest a trade‐off in which the species most proficient at acquiring P have ephemeral roots that are particularly susceptible to soil‐borne pathogens. This could equalize out the differences in competitive ability among co‐occurring species in these ecosystems, thus contributing to coexistence. Moreover, effective protection against soil‐borne pathogens by ectomycorrhizal (ECM) fungi might explain the occurrence of monodominant stands of ECM trees and shrubs amongst otherwise species‐rich communities. We identify gaps in our knowledge which need to be filled in order to evaluate a possible link between P limitation, fine root traits, soil‐borne pathogens and local plant species diversity. Such a link may help to explain how numerous plant species can coexist in hyperdiverse rainforests and shrublands, and, conversely, how monodominant stands can develop in these ecosystems.